Private vs public care for intracranial tumours: Findings from Pakistan - Mashal Murad Shah; Mohammad Hamza Bajwa; Muhammad Usman Khalid; Rashid Jooma; Erum Baig; Altaf Ali Laghari; Naveed Zaman Akhunzada; Saad bin Anis; Muhammad Faraz Raghib; Sameen Siddiqi; et al. (Journal of the Pakistan Medical Association, 2022)
Objective: To observe the patient characteristics and centres providing neuro-oncological care in public and private health hospitals in Pakistan. Methods: The Pakistan Association of Neuro-oncology carried out a retrospective, cross-sectional study in 2019 on patients admitted to 32 hospitals in Pakistan, with dedicated neurosurgical facilities. Patients with a histopathological diagnosis of an intracranial tumour were included. Results: Public health care facilities catered for 84% patients with ages between 20 and 60 years and children having intracranial tumours. Private centres were utilised by 66.7% patients from the upper socioeconomic sector. More patients were lost to follow-up in the public sector (n = 784) versus in the private sector (n = 356). Mortality was also higher in the public sector hospitals, (13.9%) as compared to 9.6% in the private sector. Conclusion: Public and private sector health services for neuro-oncological care in Pakistan still have a long way to go to cover the gaps for unmet needs. Strengthening health systems for brain tumour care is imperative to increase both the access to care and the quality of care to fulfil this need. Keywords: Retrospective study, Health systems, Brain neoplasms, Health care, Epidemiology, Chemoradiotherapy.